Análise qualitativa de estratégias inovadoras no ensino de matemática - Santos, Patrícia Mendonça Talmelli dos (2020)
In this study, the author shows application of innovative activities and methodologies in the teaching of ratios in the 6th year of elementary school, the school where the research teacher works. The choice of the theme came from the researcher's observation of the difficulties presented by elementary school students in understanding techniques and valuing the use of mathematical tools such as proportion and percentage in everyday life. The purpose of the activities was to support the teaching of ratios and proportions using methodologies that provide cognitive and socioemotional structures so that learning takes place in an organic and meaningful way, thus students get opportunities of experiences during the didactic sequence so that they can maintain learning for all their life. The activities followed the course of Didactic Engineering as a research methodology.